How students of primary school understand large scale energy systems: The case of thermal power plant - Niki Sissamperi; Dimitris Koliopoulos (OmniaScience, 2021)
The aim of this study is to investigate the impact of a constructivist teaching intervention on 6th grade students' cognitive progress on large-scale Energy Generation Systems (EGS), specifically on a Thermal Power Plant (TPP). This intervention was designed according to the constructivist approach for teaching and learning science, and it can be described as an autonomous teaching module appropriate for an elementary science curriculum. With the application of this intervention in real classroom settings, the majority of students were able to construct sufficient technological and scientific knowledge in order to describe and explain the operation of a TPP in qualitative energy terms, as our research data ascertained.